Naphtha desulfurization by prepare Cu-Ni-zeolite adsorbent - A. Mohammed, Abdul-Halim; A. Abdulwahhab, Maha (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
For desulfurization of naphtha, NaY zeolite was prepared from Dewekhala kaolin clay (Al-Anbar region). For the prepared zeolite adsorbent, x-ray diffraction, sodium content, silica to alumina ratio, surface area, bulk density and crushing strength were determined. From the x-ray diffraction of the prepared NaY zeolite and by a comparison with the standard NaY zeolite, it was found that the prepared adsorbent in this work has approximately the same crystal structure as the standard. Adsorption process was done in a laboratory unit at 25 ᵒC and 4.1 h-1 LHSV. The experimental results show that the promoted adsorbent gives higher percentage of sulfur removal (82.15%) after 10 minute and reaching 40.15% after 120 minute. The adsorption capacity is equal 0.167 mmole "S"/ g after 10 minute while it reached up to 0.77 and 0.98 mmole "S"/g at 50 and 120 minute, respectively.